Effect of sera from lupus patients on the glomerular endothelial fibrinolysis system. Issue 1 (6th May 2022) - Sato, Riko; Aizawa, Tomomi; Imaizumi, Tadaatsu; Tsugawa, Koji; Kawaguchi, Shogo; Seya, Kazuhiko; Terui, Kiminori; Tanaka, Hiroshi
Abstract: Background: Dysregulation of the coagulation fibrinolysis system in resident glomerular cells is associated with the pathogenesis of lupus nephritis. However, the role of plasminogen activator inhibitor‐1 (PAI‐1) and tissue plasminogen activator (tPA) in resident glomerular cells remains undetermined. Methods: We examined the expression of PAI‐1 and tPA mRNA in cultured normal human glomerular endothelial cells (GECs) treated with serum from patients with systemic lupus erythematosus (SLE) using quantitative reverse transcription polymerase chain reactions. We determined the relationship between PAI‐1/tPA mRNA expression and several clinical/laboratory parameters. Serum from 16 patients (nine patients with new‐onset SLE and seven patients with stable SLE) was used in the study. Results: Plasminogen activator inhibitor‐1 and tPA mRNA expression was significantly higher in GECs treated with serum of patients with new‐onset SLE than other groups. The PAI‐1 and tPA mRNA levels were also significantly correlated in GECs treated with serum from patients with SLE. Interestingly, both PAI‐1 and tPA mRNA levels in GECs were inversely correlated with serum C4 level and positively correlated with SLE disease activity. Conclusions: These results suggest that serum from patients with SLE may activate the fibrinolysis system in glomerulus, which may be involved in the pathogenesis of lupus nephritis.